2002
DOI: 10.1046/j.1365-2761.2002.00343.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and pathogenicity of a grouper iridovirus (GIV) isolated from yellow grouper, Epinephelus awoara (Temminck & Schlegel)

Abstract: Molecular characterization was carried out on an iridovirus isolated from yellow grouper, Epinephelus awoara. The major capsid protein (MCP) gene was located, sequenced and compared with homologous genes from other iridoviruses. The nucleotide sequence is 1392 bases long and contains a single open reading frame beginning at an ATG codon from the 5′ end and terminating at a TAA codon at the 3′ end. The open reading frame encodes a protein of 463 amino acids with a predicted molecular weight of 50 272 Da. Pairwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 26 publications
2
48
0
Order By: Relevance
“…Also, the insertion of striped electron-dense material into empty capsids (Qin et al 2001) was different from our observation for TGIV. Another iridovirus closely related to FV3 was also isolated from yellow grouper E. awoara in Taiwan (Murali et al 2002). The high similarity between the available gene sequences from TGIV and ISKNV, and the low similarity between the MCP sequences of either SGDV or the yellow grouper iridovirus to ISKNV, suggest that these iridoviruses are different from TGIV.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the insertion of striped electron-dense material into empty capsids (Qin et al 2001) was different from our observation for TGIV. Another iridovirus closely related to FV3 was also isolated from yellow grouper E. awoara in Taiwan (Murali et al 2002). The high similarity between the available gene sequences from TGIV and ISKNV, and the low similarity between the MCP sequences of either SGDV or the yellow grouper iridovirus to ISKNV, suggest that these iridoviruses are different from TGIV.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, SCRV and FV3 have been repeatedly detected among hatchery-reared freshwater fi shes in North America and Asia (Woodland et al 2002b ;Prasankok et al 2005 ;Deng et al 2011 ;George et al 2014 ;Chinchar and Waltzek 2014 ;Waltzek et al 2014 ). Two genetically distinct but related ranaviruses, Singapore grouper iridovirus (SGIV) and grouper iridovirus (GIV), have negatively impacted grouper mariculture in Asia since the 1990s (Chua et al 1994 ;Murali et al 2002 ;Qin et al 2003 ). The reasons for the emergence of ranaviruses as pathogens of fi nfi sh within both natural and managed populations are unknown.…”
Section: Ranaviruses Infecting Fishmentioning
confidence: 99%
“…Exceptions include two related ranaviruses, SGIV and GIV, which signifi cantly impact grouper mariculture in Asia (Chua et al 1994 ;Murali et al 2002 ;Qin et al 2003 ). Phylogenetic analysis based on the 26 conserved iridovirus genes demonstrated that GIV and SGIV are each other's closest relatives; however, these viruses are genetically divergent from other ranaviruses (Eaton et al 2007 ).…”
Section: Taxonomically Unassigned Ranaviruses That Affect Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…Iridovirus infection of fish and frogs is a serious problem in modern aquaculture, fish farming, and wildlife conservation because of its epidemic morbidity and ability to cause mortality. Systemic iridoviral infections have been previously described for a variety of freshwater and marine food fish species (18,22,32,37), tropical freshwater ornamental fish (40), frogs (20), and salamanders (30). Since the discovery of the first fish iridovirus, LCDV (lymphocystis disease virus), in 1962 (56), many new iridoviruslike pathogens have been reported from over 140 different species of fish worldwide (15).…”
mentioning
confidence: 99%